HAK DAN KEWAJIBAN PENGGUNA TENAGA LISTRIK DI KABUPATEN MALINAU YANG TIDAK SEIMBANG SERTA AKIBAT HUKUMNYA - Dimas Gatot Suseno (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT  The complaining of consumers of electricity in the case of careless and or breaching of the State Electricity Enterprise (PT PLN) the district East and North Kalimantan (APJ Wilayah Kalimantan Timur and the area of North Berau,  the Rayon of Malinau, namely the Fluctuation or the increasing of high voltage. The immediate high voltage being occured immediately caused a hundred of electronic equipments  such as refrigerator, television and VCD player being damaged even some of them were burnt; The electricity was off immediately without being informed in advanced by the State Electricity Enterprise (PLN); The increasing of basic electricity (TDL) done once in quaterly. If it is connected to the consumer’s rights of getting the electricity with the reasonable tariff concerning Article 34 Paragraph 1(c), therefore the increasing of basic electricity (TDL) once in quaterly  is not really reasonable, in connection with the level of income of community is not increased once in quaterly. Let`s take for instance, in a year, we are not certain the income of community would be increas in or not; The callculating of electricity tariff is not suitable with the usage of consumers. This case could be existed due to the fault of recording of bill, caused by marking up of bill due to the usage of system of former illegal bill being made. The increase of the electricity tariff is more than 30% (thirty percent), the business charging of housing and others; More over the case of requiring the decreasing of power it takes a long time being realized, for instance from 1.300 Kwh reducing it to 900 Kwh or reducing 900 Kwh to 450 Kwh. It is obvious breaking the rights of comsumers namely choosing substances and or services; The diconnected of electric currentbeing done by a singlely side. In this case the consumer should have the returning of consumer’s guarantee service fee in accordance with Article 7, Paragraph (5) SPJBTL.          Being able to demand from his rights on compensation, consumers, either alone or in unison via their lawyer are able to demand their rights on guarantee by the ways of :  Visiting, discussing and overcoming  its themself directly with the State Electricity Enterprise (PT PLN); by bringing an accusation to “YLKI”; going the tough ligitation via the District Court where the accusation being able to be done based on breach (wanprestasi) an or the action of against the law.          Hindrances which are appearing for the afford of doing the accusation against the Limited State Electricity Enterprise (PT PLN), among others :  There is a standardization of Minimal Service  Area of (SPM) which is belonging to “PT PLN” (Persero), “APJ”  District of East  Kalimantan and North one. the area of Berau, Rrayon of Malinau, causing a difficulty for the enterprise being accused on the black out of electricity within less than 3 x 24 (three times twenty-four) hours incessantly. Consumers have a passive attitute and not very cooperative during the process of doing the accusation with the “PT PLN” on mediating. This case caused the process of being stopped without being overcome; The consumers “are not brave enough” to go forward to continue their accusation via the court. Less of knowledge of conssumers concerning their rights and responsibility as well as the affords of what they are able to do when they have some disadvantages being caused by the PT PLN.  Keywords :  breach,  State Electricity Enterprise (PLN), basic electricity (TDL), high voltage, Indonesian Institute of Consumer (YLKI).